Investigation of chemical treatability of effluent water in Istanbul-Baltalimani Preliminary Mechanical Treatment Plant - Debik, E; Demir, A; Toröz, I; Günay, A (INST LEBENSMITTELTECHNOLOGIE ANALYTISCHE CHEMIE, 1999)
In recent years, not only physical and biological processes but also chemical operations have been used in sewage treatment. In previous studies, more than 80% of organic substances and 90% of phosphorus removal were succeeded with chemical addition in sewage treatment. In this study, chemical treatability of sewage water was investigated by performing a series of experiments on sewage water taken from Baltalimani Mechanical Treatment Plant of Istanbul and treatment alternatives before marine discharge were suggested on the basis of the results obtained.
Keywords: chemical wastewater treatment; jar test; coagulation; flocculation; WASTE-WATER; Environmental Sciences & Ecology